2010
DOI: 10.1159/000313823
|View full text |Cite
|
Sign up to set email alerts
|

Residual Cancer Stem Cells after Interval Cytoreductive Surgery following Neoadjuvant Chemotherapy Could Result in Poor Treatment Outcomes for Ovarian Cancer

Abstract: The objective of this review is to discuss the common surgical strategy of cytoreductive surgery after neoadjuvant chemotherapy, with an emphasis on incorporating extensive cytoreductive surgery to remove traces of regressed tumor. A review of the literature regarding cytoreductive surgery after neoadjuvant chemotherapy and cancer stem cells is given together with the authors’ own experience and comments. Most ovarian cancer cells consist of transformed cells that regress after neoadjuvant chemotherapy. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 38 publications
(51 reference statements)
1
57
0
Order By: Relevance
“…Chemoresistance of ovarian cancer may be induced by NAC [13], leading to a bad prognosis if recurrence occurs. Although the diameter of metastatic tumor could be reduced by NAC, even to less than 1 cm, the tumor tissue may contain cancer stem cells, which is responsible for chemotherapy-resistant recurrence [14]. Meanwhile, because of the chemotherapy prior to surgery, the planned cycles of postsurgical chemotherapy may be less in NAC group than PDS group.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoresistance of ovarian cancer may be induced by NAC [13], leading to a bad prognosis if recurrence occurs. Although the diameter of metastatic tumor could be reduced by NAC, even to less than 1 cm, the tumor tissue may contain cancer stem cells, which is responsible for chemotherapy-resistant recurrence [14]. Meanwhile, because of the chemotherapy prior to surgery, the planned cycles of postsurgical chemotherapy may be less in NAC group than PDS group.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, he was able to conclude that primary cytoreductive surgery offers an increased survival for patients compared to NACT in the absence of RT and when RT < 1 cm. It is worth noting that for the patients in the neoadjuvant therapy group, the fact that they were diagnosed as non-resectable gives them a worse prognosis, probably because of the tumor's intrinsic biology and tumor stem cells' resistance to chemotherapy [7,37], regardless of the surgery that may be performed. As a consequence, the results of all nonrandomized studies show a certain bias, given that patients with multiple comorbidities or patients with the worse ECOG Score, or the highest tumor burden are usually assigned to the interval surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…A population of chemotherapy-resistant stem cells selected during NACT and not debulked in IDS may play a role in EOC recurrence. It was suggested that all tissue showing traces of tumor, that is, scar tissue, should be removed during IDS [Lim et al 2010]. More recently, another author reported that TP53-K351N mutation was involved in platinum resistance after NACT [Zhang et al 2014].…”
Section: Platinum Resistancementioning
confidence: 99%